Platelet-derived growth factor levels in Iraqi multiple myeloma patients: a case-control study - Ramadan, Ghazi Mohamad; Al-Sadi, Hafidh I.; Alkafaji, Saja I.; Al-Hindy, Hayder Abdul-Amir Makki; Mousa, Mazin Jaafar; Jawad, Heba S.; Chabuk, Shahlaa Kh.; Abbas, Rana J.; Ali, Hasan Abd; Makki, Mina Mohammed; Hadi, Fatima Hussein; Dawood, Noor Alhuda Tahreer (Pharmakeftiki, 2025)
Multiple myeloma (MM), the second most prevalent haematological malignancy, is characterized by monoclonal plasmacytosis within the bone marrow. Platelet-derived growth factor (PDGF), a key mediator of angiogenesis and tumorigenesis, has been implicated in the pathophysiology of MM. This study aimed at investigating whether pre-treatment serum levels of PDGF correlate with MM diagnosis, disease stage, and therapeutic response. A case-control study was conducted involving 55 Iraqi patients diagnosed with MM and 25 healthy controls. Participants were recruited from the Department of Haematology at the Marjan Medical Hospital, Babil Province, Iraq, between March 2021 and December 2022. Serum PDGF concentrations were quantified using enzyme-linked immunosorbent assay (ELISA). MM patients exhibited higher mean PDGF levels than controls (mean difference: 187.3 pg/mL), although this difference did not reach statistical significance (p=0.077). Among MM patients, those receiving treatment demonstrated significantly lower platelet counts (p=0.012) and elevated serum urea levels (p=0.045) compared to untreated counterparts. Receiver operating characteristic (ROC) curve analysis revealed poor diagnostic accuracy of PDGF for MM (area-under-the-curve; AUC: 0.575; p=0.030), as well as limited discriminatory power between stage II and stage III disease (AUC: 0.586; p=0.059). In conclusion, although serum PDGF levels alone do not constitute a statistically significant or specific diagnostic biomarker for MM, the findings underscore the need for further investigation into the combined utility of PDGF and other molecular markers to improve diagnostic and prognostic stratification in MM.